Research progress on the adverse effects of high-altitude environment to the male reproductive system: a review study - Meng, Dong-Dong; Kang, Yin-Dong; Chang, De-Hui (Frontiers in Endocrinology, 2025)
An increasing number of people are being exposed to high-altitude environments as they become more important in economic development, resource exploitation, and other areas. This review is focused on the impact of the high-altitude environment on the male reproductive system. In high-altitude areas, the unique conditions lead to complex and significant changes in male reproductive hormone levels. The secretion of GnRH is inhibited, which in turn affects the levels of FSH and LH, ultimately influencing testosterone synthesis and secretion, thus disrupting the normal endocrine regulatory network. Testicular tissue also shows marked morphological changes. The seminiferous tubule structure becomes disordered, and the number and function of spermatogenic and interstitial cells are damaged. These alterations have a direct impact on sperm quality, resulting in a decrease in sperm density and motility, an increase in the deformity rate, and damage to genetic material integrity. Additionally, sexual function is affected, with symptoms such as decreased libido and erectile dysfunction being common. The underlying mechanisms involve oxidative stress damage, an abnormal increase in apoptosis, and enhanced autophagy. Nevertheless, current research, especially human-based studies, is restricted by small sample sizes and insufficiently in-depth exploration of these mechanisms.